Case report: Reversible encephalopathy associated with liposomal amphotericin B in a patient with cryptococcal meningitis - Luo, Si; Wen, Han; Zhou, Meihong; Wu, Chengsi; Hong, Daojun (Frontiers in Neurology, 2022)
Liposomal amphotericin B (L-AMB) is an anti-fungus medicine that has fewer side effects than traditional amphotericin B (AMB). Neurotoxicity of L-AMB has rarely been observed, and only one case of leukoencephalopathy during intravenous L-AMB has been reported. Herein, we described a patient with cryptococcal meningitis presenting with late-onset reversible encephalopathy associated with liposomal amphotericin B.